Diagnostic Accuracy of Holotranscobalamin, Vitamin B12, Methylmalonic Acid, and Homocysteine in Detecting B12 Deficiency in a Large, Mixed Patient Population. (7th February 2020) - Jarquin Campos, Araceli; Risch, Lorenz; Nydegger, Urs; Wiesner, Jacobo; Vazquez Van Dyck, Maclovia; Renz, Harald; Stanga, Zeno; Risch, Martin
Abstract : Four biomarkers are commonly employed to diagnose B12 deficiency: vitamin B12 (B12), holotranscobalamin (HoloTC), methylmalonic acid (MMA), and homocysteine (Hcy). 4cB12, a combined index of the B12 status, has been suggested to improve the recognition of B12 deficiency. We aimed to evaluate the four different markers for detecting B12 deficiency, as determined by 4cB12. Within a large, mixed patient population, 11, 833 samples had concurrent measurements of B12, HoloTC, MMA, and Hcy. 4cB12 was calculated according to the methods described by Fedosov. Diagnostic cutoffs as well as diagnostic accuracy for the detection of B12 deficiency were assessed with receiver operating characteristic (ROC) analysis. The median age was 56 years, and women accounted for 58.8% of the samples. Overall, the area under the curve (AUC) for the detection of subclinical B12 deficiency was highest for HoloTC (0.92), followed by MMA (0.91), B12 (0.9) and Hcy (0.78). The difference between HoloTC and B12 was driven by a significantly higher AUC for HoloTC (0.93) than for B12 (0.89), MMA (0.91), and Hcy in women 50 years and older (0.79; p < 0.05 for all). In the detection of subclinical B12 deficiency, there were no significant differences in the AUCs of HoloTC, B12, and MMA among men and women <50 years. In conclusion, in women < 50 years and in men, HoloTC, MMA, or Hcy do not appear superior to B12 for the detection of B12 deficiency. For women 50 years and older, HoloTC seems to be the preferred first-line marker for the detection of subclinical B12 deficiency.